A mata em movimento: coroa portuguesa, senhores de engenho, homens livres e a produção do espaço na Mata Norte de Alagoas - Andrade, Juliana Alves de (2008)
In this study, we propose to make a study of the area as a historic building. Thus, we believe that the spaces are built from a complex network of sociability and power, where a particular social group seeks exert power over the region and define its forms of production, making the daily lives of other rural social segments a field of confrontations. These forces can be scaled by the study of spatial configurations and historic culture, since these mechanisms can vary with the gimmicks that each of these groups have to materialize their practices for the production of space. Therefore, to understand these disputes, we choose the Forest north, of the state of Alagoas between the end of the eighteenth century and the first three decades of the nineteenth and its main stakeholders: the Portuguese Crown; owners, especially the gentlemen of ingenuity and the free and poor population; the Indians and maroon, examining the tactics and strategies developed by each of these social follow through data in inventories, wills, reports from the administration of the Portuguese Crown and memories travelers.